RNA silencing in plant symbiotic bacteria: Insights from a protein-centric view. Issue 12 (2nd December 2017) - Jiménez-Zurdo, José I.; Robledo, Marta
ABSTRACT: Extensive work in model enterobacteria has evidenced that the RNA chaperone Hfq and several endoribonucleases, such as RNase E or RNase III, serve pivotal roles in small RNA-mediated post-transcriptional silencing of gene expression. Characterization of these protein hubs commonly provide global functional and mechanistic insights into complex sRNA regulatory networks. The legume endosymbiont Sinorhizobium meliloti is a non-classical model bacterium with a very complex lifestyle in which riboregulation is expected to play important adaptive functions. Here, we discuss current knowledge about RNA silencing in S. meliloti from the perspective of the activity of Hfq and a recently discovered endoribonuclease (YbeY) exhibiting unprecedented catalytic versatility for the cleavage of single- and double-stranded RNA molecules.